Defense of the Constitution or of constitutionality? - Palomino Manchego, José Félix (2021)
This paper focuses on the analysis of article 38 of the Political Constitution of Peru of 1993, which establishes as a duty of all Peruvians to honor Peru, protect national interests, as well as to respect, comply with and defend the Constitution and the country’s legal system. It should be emphasized that the latter requires precision as to the institutions it protects, distinguishing between the Constitution, as a rule of rules, and constitutionality, which represents the essential principle under which modern democracies are built. In this manner, the mechanisms established for the defense of the normative hierarchy of the Constitution are reviewed, as well as the need to forge a committed culture, patriotism, and constitutional sentiment.